Colopleural fistula due to strangulated Bochdalek hernia in an adult. Issue 9 (September 1989) - Sinha, M; Gibbons, P; Kennedy, S C; Matthews, H R
Abstract : An elderly patient presented with a right sided pneumothorax due to strangulation of part of the colon through a congenital Bochdalek hernia. Congenital posterolateral diaphragmatic hernia of Bochdalek is rare in an adult and strangulation with pneumothorax has not been reported before.